2015
DOI: 10.1080/17686733.2015.1013663
|View full text |Cite
|
Sign up to set email alerts
|

Defect depth quantification using lock-in thermography

Abstract: In this paper we explore the defect evaluation in austenitic stainless steel (SS) using Lock-in technique and the effect of modulation frequency on defect detectability. A review of international literature indicates that while such studies have been attempted on materials like Perspex and composites, studies on austenitic SS like AISI 316, which are widely used in nuclear and other process industries, have been limited. For depth quantification, blind frequency method and phase contrast method have been discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 18 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…A frequency of 0.2 Hz is chosen. At this frequency the heat wave penetration is approximately the thickness of the board [4].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…A frequency of 0.2 Hz is chosen. At this frequency the heat wave penetration is approximately the thickness of the board [4].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…C. Manyong et al [ 44 ] and L. Junyan et al [ 45 ] used LIT to evaluate the FBH defects in steel structure and showed that the phase angle differences between the defective regions and sound regions provide the defect location and size. D. Sharath et al [ 46 ] studied on the blind frequency and phase contrast methods to evaluate the artificial square, rectangular and circular defects in austenitic stainless steel using LIT. It was concluded that blind frequency is dependent on the defect size and shape and could not be applied for depth quantification unless a normalization method is used.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed (PT) [7,8,9,10,11,12] and lock-in (LT) [13,14,15,16,17,18,19,20,21,22] thermography are the techniques used in the last years for defect depth, thickness or more in general defect/damage measurement.…”
Section: Introductionmentioning
confidence: 99%